Short Communication: Helminth fauna of Lutjanidae from Kedonganan, Bali, Indonesia - ERICK ARRASHY RUDIANTO; DIAH PERMATA WIJAYANTI; DWI HARYANTI; ELIS INDRAYANTI (Society for Indonesian Biodiversity, 2024)
Abstract. Rudianto EA, Wijayanti DP, Haryanti D, Indrayanti E. 2024. Short Communication: Helminth fauna of Lutjanidae from Kedonganan, Bali. Biodiversitas 25: 4986-4993. The biodiversity of parasites in demersal reef fishes is immense but remains poorly understood and often overlooked. This is also hindered by the lack of survey of parasite communities in reef fishes, especially in Indonesia. Therefore, we surveyed endoparasites of reef-associated and demersal lutjanids in the Kedonganan fish market, Bali. A total of 25 individuals of six lutjanid species: Lutjanus erythropterus, Lutjanus russellii, Lutjanus sebae, Lutjanus timoriensis, Lutjanus vitta, and Pristipomoides multidens, were collected from the fish market. The parasites were collected using a modification of the gut wash method. Two individuals of Philometridae were recovered from L. vitta. Other recovered helminth fauna were Acanthocephala, Nematoda, and Digenea, mainly belonging to Siphoderina spp. and Hamacreadium sp. We also reported for the first time, endoparasites of L. erythropterus and P. multidens in Indonesian waters. This study highlighted the importance ichthyo-parasitological survey as a part of the biodiversity survey. More surveys and reports on endoparasites in demersal reef fishes in Indonesia are needed, especially on their biology, ecology, diversity, and impact on human health, considering that most of these demersal fishes are consumed by local people.